The effects of washing with Tamarind (Tamarindus indica L.) water solution on shelf life of silver carp (Hypophthalmichthys molitrix) fillet during refrigerator storage - Eshagh Zakipour Rahimabadi; Mehri Zolfaghari; Mahin Rigi (International Journal of Aquatic Biology, 2016)
This study evaluated the antibacterial and antioxidant effects of tamarind water solution on shelf life of silver carp (Hypophthalmicthys molitrix) fillet during refrigerator storage. Treatments of this study were unwashed samples (control), and samples washed with 1% and 2% tamarind water solution. Microbial, physicochemical and sensory analysis including total viable count (TVC), peroxide value (PV), thiobarbituric acid (TBA), total volatile base (TVB-N) and pH were measured during 15 day storage at refrigerator (with 3 days intervals). Proximate analysis of samples also measured at day 0. TVC content was 0.93, 0.50 and 0.10 log CFU/g for control and treatments 1% and 2%, respectively and reached to 6.24, 5.82 and 5.21 log CFU/g at the end of storage period. At the end of storage period, the PV, TBA and TVB-N content were 8.4, 4.3, and 3.0 meq O2/Kg for control, 2.75, 1.35, and 0.50 mg/100g for 1% treatment, and 33.17, 23.90, and 22.10 mg N/100g for 2% treatment, respectively. This results showed the positive effect of tamarind to inhibit and delay fish fillet spoilage. According to sensory evaluation, the density of 1% tamarind was selected as the best density.